2021
DOI: 10.1021/acscentsci.1c00039
|View full text |Cite
|
Sign up to set email alerts
|

Potent Noncovalent Inhibitors of the Main Protease of SARS-CoV-2 from Molecular Sculpting of the Drug Perampanel Guided by Free Energy Perturbation Calculations

Abstract: Starting from our previous finding of 14 known drugs as inhibitors of the main protease (Mpro) of SARS-CoV-2, the virus responsible for COVID-19, we have redesigned the weak hit perampanel to yield multiple noncovalent, nonpeptidic inhibitors with ca. 20 nM IC50 values in a kinetic assay. Free-energy perturbation (FEP) calculations for Mpro-ligand complexes provided valuable guidance on beneficial modifications that rapidly delivered the potent analogues. The design efforts were confirmed and augmented by dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
316
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(348 citation statements)
references
References 29 publications
6
316
0
3
Order By: Relevance
“…One strategy for designing novel, drug-like, noncovalent compounds is the optimization of low-affinity hits that are existing drugs with known pharmacokinetic properties. We have previously reported the optimization of the antiepileptic drug perampanel, initially identified in a virtual screen, from a weak inhibitor of M pro (half-maximal inhibitory concentration [IC 50 ] 100–250 μM), to several lead compounds with activities in the low-nanomolar range by means of an iterative approach complementing free-energy perturbation calculations and compound synthesis with structural characterization ( Ghahremanpour et al., 2020 ; Zhang et al., 2021 ). Moreover, this lead optimization approach yielded compound 26 , which showed promising antiviral activity (half-maximal effective concentration [EC 50 ] 2.0 ± 0.7 μM) and cytotoxicity (half-maximal cytotoxic concentration [CC 50 ] >100 μM) ( Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One strategy for designing novel, drug-like, noncovalent compounds is the optimization of low-affinity hits that are existing drugs with known pharmacokinetic properties. We have previously reported the optimization of the antiepileptic drug perampanel, initially identified in a virtual screen, from a weak inhibitor of M pro (half-maximal inhibitory concentration [IC 50 ] 100–250 μM), to several lead compounds with activities in the low-nanomolar range by means of an iterative approach complementing free-energy perturbation calculations and compound synthesis with structural characterization ( Ghahremanpour et al., 2020 ; Zhang et al., 2021 ). Moreover, this lead optimization approach yielded compound 26 , which showed promising antiviral activity (half-maximal effective concentration [EC 50 ] 2.0 ± 0.7 μM) and cytotoxicity (half-maximal cytotoxic concentration [CC 50 ] >100 μM) ( Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the optimization of the antiepileptic drug perampanel, initially identified in a virtual screen, from a weak inhibitor of M pro (half-maximal inhibitory concentration [IC 50 ] 100–250 μM), to several lead compounds with activities in the low-nanomolar range by means of an iterative approach complementing free-energy perturbation calculations and compound synthesis with structural characterization ( Ghahremanpour et al., 2020 ; Zhang et al., 2021 ). Moreover, this lead optimization approach yielded compound 26 , which showed promising antiviral activity (half-maximal effective concentration [EC 50 ] 2.0 ± 0.7 μM) and cytotoxicity (half-maximal cytotoxic concentration [CC 50 ] >100 μM) ( Zhang et al., 2021 ). This effort provides the most extensive description to date of several noncovalent inhibitors of M pro derived from an FDA-approved chemical scaffold with in vitro activities that improve upon activities of recently described covalent inhibitors ( Dai et al., 2020 ; Zhang et al., 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic patches are found at the Mpro binding site, in particular at S1, S2 and S4 subsites, and hydrophobic interactions have been extensively targeted in several studies to improve binding affinities of inhibitors towards Mpro [ [46] , [47] , [48] , [49] ].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action of a covalent inhibitor, such as N3, containing carbonyl groups [ 54 ] or Michael acceptors [ 55 ], consists in blocking the activity of the cysteine protease covalently, modifying the catalytic Cys145 residue in the S1’ region [ 48 ]. Several publications reported covalent inhibitors that target the catalytic cysteine, while other studies identified non-peptide and non-covalent inhibitors, such as compound 1 [ 47 ] ( Fig. 3 ), that claim the active site region hampering the proteolytic activity of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Glutamine at the P1 position is crucial for proteolysis to occur. As there are no known native human enzymes with such cleavage sites, M pro looks to be an ideal drug target, since there is a low risk for toxic effects on host cells [ 31 , 32 , 33 ]. Structural data on the enzyme is available and reporter assays developed making this target suitable for novel antiviral design [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%